ON THE STRUCTURE AND MECHANICAL BEHAVIOUR OF THE EXTENDING LITHOSPHERE IN THE BAIKAL RIFT FROM GRAVITY MODELLING - Petit C.; Déverchère J.; Burov E. (My University, 1997)
The crustal structure and lithospheric flexure of the Baikal Rift Zone, Siberia, are examined by means of gravity modelling. We model the Bouguer Anomaly (BA) along five 1200 km long gravity profiles. We first evidence that continuous elastic plate flexure due to surface loading cannot explain the observed BA. Then we introduce plate discontinuities coupled with a realistic brittle-elasto-ductile plate rheology, which allow us to model of external tectonic forces acting on the plates and determination of the Moho geometry. We show that the clearest expression of extensional processes occurs in the central part of the rift, which exhibits the highest crustal thinning. It evolves southwards to a rapidly increasing compression, resulting in an overthickening of the southern plate's crust and in the long-wavelength flexure of the Siberian plate. North of the central rift, crustal thinning (which is always less than 7 km) gives way to a more diffuse zone of deformation inside the Sayan-Baikal folded belt. Based on plate flexure models, we propose that the rift shoulders surrounding the central and north Baikal basins are not supported by upward bending plate, but have a deep crustal root caused by a downward flexure. The other parts of the rift depict two adjacent plates with antithetic flexures. We also infer that the axial mantle material upwarping is not related to a large-scale asthenospheric upwelling, since the lithosphere rheological interfaces are not significantly disturbed.Our results favour the role of horizontal forces and motions, resulting from the India-Asia collision, combined with the effect of inherited tectonic structures (and especially the Paleozoic suture bounding the Siberian craton) for explaining the crustal structure and plate flexure modeled.
Keywords: Paleozoic; Paleozoic; Палеозой